(untitled) (Nigerian Journal of Technology, 2008)
A study was undertaken to determine the geotechnical properties of Makurdi shale. Seven disturbed soil samples were collected from two sites in Makurdi and subjected to engineering classification tests and X-ray diffraction analysis. Results of the simple index tests suggest that the soils have medium to high swelling potential while X-ray diffraction analysis showed that the soils contain a high percentage of mixed-layer illite/smectite, high percentage of kaolinite and a small percentage of illite. The mineralogical analyses explained the expansive nature of the soil and suggest the causes of cracks in buildings. Ten disturbed soil samples were collected from a third site of a proposed site for a light building and subjected to engineering classification tests. Based on the outcome of the second set of experiments, a foundation other than the conventional strip footing was proposed and constructed. The performance of the foundation was observed for 5 cycles of rainy and dry seasons and found to be very satisfactory; as very few cracks were observed compared to light buildings founded on similar sites. It can be concluded that the proposed foundation appears to be suitable for light buildings on expansive clays and is therefore recommended as a solution to the problem of foundations on such soils.